The Role of Third Parties in the Joint Comprehensive Plan of Action (JCPOA) Negotiation Process 2003-2015 - Qory Fizrianti Beru Sitepu (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
This article analyses the JCPOA negotiation process using the Third Side Negotiation Theory by mapping three key stages: preventing, resolving, and containing. Using a qualitative case study design, with a deductive approach, this study draws on official JCPOA texts, UNSC resolutions, IAEA reports, policy documents, and secondary academic sources. The findings show that the success of the JCPOA is inseparable from the intervention of third parties—particularly the UNSC, E3, and IAEA—who played pivotal roles in preventing escalation, mediating diplomatic deadlocks, and monitoring compliance throughout the negotiation period. The study contributes to negotiation and conflict-resolution scholarship by demonstrating how third-party intervention can transform high-risk geopolitical confrontation into a cooperative, rule-based agreement, with implications for future nuclear diplomacy frameworks and multilateral negotiations involving asymmetric power relations.